CHALLENGES FOR FUTURE TEACHERS IN INCLUSIVE SCHOOLS - Rohmatillah, Layli; Jannah, Ulfa Qomariatul; Sanjani, M Aqil Fahmi (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Every citizen has the same right to receive education, including students with special needs. One of the strategic steps the government takes to provide equal access to quality education for all its citizens is implementing inclusive education at all levels. In this study, the author uses a literature review approach. Based on the results of the literature review, it was found that teachers with all their competencies and resources face the challenge of truly understanding the characteristics of students, which continue to develop over time. In addition, teachers are required to innovate through research activities as part of their duties in addition to teaching. Furthermore, teachers must be able to utilize existing learning communities, such as Teacher Working Groups (KKG) or other communication forums, to become more professional, inclusive elementary school teachers.